Cellular and synaptic properties of molecularly defined neurons in the external globus pallidus - Linda M.C. Koene; Wilhelm Thunberg; Sten Grillner; Gilad Silberberg; Maya Ketzef (iScience)
Summary: The external globus pallidus (GPe) is a central basal ganglia (BG) nucleus, involved in various sensorimotor functions. The two main types of GPe neurons, the prototypic and arkypallidal neurons, differ in developmental origin, axonal projections, and functional roles. Using ex vivo whole-cell patch-clamp recordings, we characterized the membrane properties, morphology, and synaptic connectivity of molecularly identified GPe neurons. Arkypallidal neurons had broader, slower action potentials with higher thresholds, and smaller somata, dendritic length, and surface area than prototypic neurons. Optogenetic activation of prototypic neurons inhibited both GPe subpopulations, but paired recordings revealed very sparse direct synaptic connectivity only between prototypic neurons. Moreover, parvalbumin-expressing prototypic neurons were not electrically coupled. This work provides a comprehensive description of the GPe microcircuitry and may provide insight into the functional role of the GPe within the BG network.